Influential factors and faculty members’ practices in technology integration using ISTE standards for teacher preparation at Taibah University- Saudi Arabia - Bajabaa, Aysha Sulaiman (Kansas State University, 2017)
Using technology effectively has been proven to enhance education. The status quo in Saudi Arabia reflects low-level usage of technology in K-12 classrooms. Preparing 21st Century teachers to integrate technology in their future classrooms for meaningful learning requires College of Education faculty to model using technology effectively. This study investigated the technology integration practices of faculty members in the College of Education at Taibah University, particularly to what extent these practices are aligned with ISTE NETS-T standards and what factors predict these practices. Based on the literature, the factors examined include attitudes towards technology use, pedagogical beliefs, technical skills, workload, professional development, technology access, technical support, and leadership support. The population of the study was the 257 faculty in the College of Education at Taibah University. The study used a web-based survey containing 66 closed-ended items to collect data, and 170 valid responses were obtained (66% response rate). Descriptive and multiple linear regression analyses were conducted to analyze data. Findings from the first research question revealed that faculty members’ technology integration practices were well-matched with ISTE NETS-T standards since the overall mean of these items was (M= 4.25, SD= .64). This indicates that faculty members had awareness of using technology effectively based on these standards to engage students in meaningful learning. Results from the multiple linear regression analysis revealed that the overall model was significant as it explains 43% of the variability in faculty members’ technology integration practices. Three significant factors statistically predicted faculty members’ technology integration practices based on ISTE NETS standards. Faculty members’ attitude toward technology had a positive relationship with faculty members’ technology integration practices [β=.35, p=.00]. Faculty technical skills had also a statistically significant positive relationship with faculty members’ technology integration practices [β=.19, p=.00]. However, leadership support was found to have a statistically significant negative relationship with faculty members’ technology integration practices in teaching based on ISTE NETS-T standards [β=-.23, p=.00]. These results, in addition to the means of the independent variables, showed that the highly rated technology integration factors, including technology attitudes and technical skills, predict their high technology integration practices based on ISTE NET-T standards. However, faculty members still need more support in several technology integration factors including professional development, technology access, workload, and leadership support. The study recommends education faculty members to model the effective use of technology for pre-service teachers through providing them with opportunities to observe it in a variety of instructional models and practice the constructivist use of technology in lesson plan assignments and projects during the program, which helps in developing positive attitudes toward technology use among pre-service teachers. College of Education leaders are recommended to have a clear shared technology vision and offer the resources and support needed to make instructional technology integration successful. Recommendations for future studies are also discussed.
Keywords: Educational technology; College of education; Saudi Arabia; Influential factors; Faculty members; International Society for Technology in Education Standards